Beyond cycles - police watchdog reform mechanics - Buckmaster, Carrie (Crime, law and social change, 2021)
This paper presents a new framework for better understanding the mechanics of police oversight reforms. It outlines a case study of New Zealand police oversight organisation reform and a comparative analysis with four other jurisdictions: England and Wales, Scotland, Northern Ireland and New York. Together these cases allow us to trace the path of police watchdog reform and demonstrate that it is not simply a series of cycles, or preordained set of management challenges. Instead it is a more complex, staggered process of reactive and proactive reform that includes reform cycles, watchdog-initiated growth, justice sector reform and the ripple effect. The paper draws upon and extends two theoretical approaches - Organisational Life Cycle theory [1, 2] and Police Complaints Reform Cycle frameworks [3] - to develop this new model of police oversight organisation reform mechanisms. Further, the paper proposes that deficits in watchdog transparency impede accountability, in turn stifling the public awareness needed for reform mechanisms to function and stunting the growth of an oversight organisation’s funding and powers.